Characteristics of Dust Accumulation and Influence on PV Panel’s Efficiency - Mohamad Ali, Ikhwan Hakim (2022)
Solar energy is a promising environmentally friendly energy. Generation of electricity by using solar PV can help in reducing the emission of green gases.